Arteriovenous malformations: assessment of gliotic and ischemic changes with fluid-attenuated inversion-recovery MRI - Essig, Marco; Wenz, Frederik; Schönberg, Stefan; Debus, Jürgen; Knopp, Michael V.; Kaick, Gerhard van (Investigative radiology, 2000)
RATIONALE AND OBJECTIVES: To evaluate the diagnostic potential of fluid-attenuated inversion-recovery (FLAIR) MRI in the assessment of patients with cerebral arteriovenous malformations (AVMs) and to correlate the MR findings with clinical symptoms, in particular, perilesional gliosis and ischemic changes. - METHODS: Forty-five patients with cerebral AVMs were examined with FLAIR and conventional T1- and T2-weighted MRI by using identical slice parameters. Images were assessed in a two-reader study for detection and delineation of gliotic and ischemic tissue. Also, the extent of the flow void phenomenon and image artifacts were evaluated. - RESULTS: FLAIR MRI was rated superior to the conventional T2-weighted fast spin-echo imaging in the assessment of intralesional and perilesional gliosis. The superior delineation was a result of the suppression of cerebrospinal fluid, mild T1 weighting, and the more pronounced flow void phenomenon. There was no significant correlation between the extent of gliosis and the clinical symptoms. However, larger AVMs had more extensive signal changes. - CONCLUSIONS: FLAIR is a valuable MRI technique to assess gliotic and ischemic changes in or close to cerebral AVMs. Because gliotic and ischemic changes are common findings and are known to be associated with epilepsy, in the assessment of these patients FLAIR is clinically useful and may guide decisions about treatment-for instance, the extent of surgical resection of the potential epileptogenic focus.
Gesehen am 21.03.2022